Power Relationships in Vote-Buying in Political Career Progression: A Rational Choice Theory Perspective - Septi Wulandari; Esa Septian; Suprapti Suprapti; Nur Baity Al Wafiroh (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2024)
The term "vote-buying" is a phenomenon that is deeply ingrained in contemporary society, resonating even with individuals who may not be well-versed in politics. The prevalence of this phenomenon typically emphasizes the extent to which the practice has become pervasive, especially during election periods. Often viewed as a convenient and strategic means of securing votes, vote-buying serves as a shortcut for individuals or parties seeking to gain power. Therefore, this research aims to examine the phenomenon of vote-buying and selling in Indonesia from a political economy perspective while also exploring the rational choices made by voters in different circumstances, specifically during regional and national elections. In order to achieve the objectives, a literature review methodology was adopted and data was sourced from articles published in reputable national and international journals. The results showed that vote-buying in Indonesia was significantly influenced by economic disparities and limited educational attainment. In this context, voters tend to prioritize immediate financial benefits to address respective basic needs. For political candidates, this practice served as a calculated strategy to gain support by exploiting the urgent economic challenges faced by the electorate. From a rational choice perspective, it was observed that voters often made decisions rooted in short-term economic considerations, rendering vote-buying a seemingly pragmatic choice in the context of both general and regional elections